Всем сестрам...: рассказы / Мария Метлицкая - Метлицкая Мария (За чужими окнами, 2012)
Экземпляры: Абонемент (20181208) / Инвентарный номер: 43427 / Цена: 192.15 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6